Penerapan Metode Naïve Bayes Dalam Memprediksi Kepuasan Mahasiswa Terhadap Cara Pengajaran Dosen - Putri Ramadani; Gunadi Widi Nurcahyo; Billy Hendrik (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Student satisfaction in higher education is the main focus in improving the quality of education. In the Tridharma paradigm, satisfaction is measured through a comparison of expectations and teaching realization as the main indicator of learning effectiveness. This research method uses Naïve Bayes classification, through the steps of reading training data, calculating prior probabilities, training data probabilities for each category, reading testing data, and calculating final probabilities. This research aims to evaluate student satisfaction with lecturers' teaching at the LP3I Polytechnic, Padang Campus. The data used in this research was 574. The results of research with 574 data (516 training and 58 testing) showed that 52 data (89.648%) stated "Very Satisfied", while 6 data (10.344%) stated "Satisfied". Prediction accuracy reached 98.28%. However, when using the Naïve Bayes method with 574 data (574 training and 574 testing), 397 data (69.078%) stated "Very Satisfied" and 177 data (30.798%) stated "Satisfied". Without the Naïve Bayes method, 402 data (69.948%) stated "Very Satisfied" and 172 data (29.928%) stated "Satisfied". An improvement of 0.87% occurred for the "Very Satisfied" category and -0.87% for "Satisfied". There are no differences in percentages for other categories. From the comparison of results, it can be seen that the Naïve Bayes method is superior in predicting student satisfaction levels compared to calculations without this method. Therefore, it can be concluded that the Naïve Bayes process model is suitable for use as a method for determining good decisions in predictions